Implementation of national standards for elementary school libraries at the state elementary school 5 Bengkulu city library - Yusuf, Salaisyah Amalia; Affandy, Dede Anisyah; Valentino, Rahmat Alifin; Igiriza, Miftahunnisa; Yolanda, Septiani; Lutfiah, Nida; Marzelena, Marzelena (Faculty of Communication, Padjadjaran University, 2025)
Background: State Elementary School 5 Bengkulu City, as a formal educational institution that has achieved A accreditation, requires a comprehensive evaluation of its library organization based on the National Standard for Elementary School/Madrasah Ibtidaiyah Libraries. Purpose: This research aims to analyze the implementation of six components of the national library standard, which include: collection standard, facilities and infrastructure standard, library staff standard, service standard, organization standard, and management standard at State Elementary School 5 Bengkulu City. Methods: This study employed a qualitative method with a case study approach. Data were collected through interview, observation, and documentation techniques. Data analysis was conducted through data reduction, data display, and conclusion drawing. Results: The research findings indicate that the library of State Elementary School 5 Bengkulu City is not yet fully compliant with the National Standard for Elementary School/Madrasah Ibtidaiyah Libraries. Of the six standards, only a few components approached [or: partially met] the established provisions. Sub-standards that were met include: minimum collection size, library area, number of library staff, vision and mission, mandatory reading program, and service reporting. Sub-standards not yet met include: advanced collection [or: further collection development, supplementary collection], facilities and infrastructure, reference and literacy services, professional staff, National Library Number (NPP) [Nomor Pokok Perpustakaan; could also be rendered as Principal Library Number or Library Identification Number], and library budget. This research concludes that the implementation of the National Standard for Elementary School/Madrasah Ibtidaiyah Libraries at SDN 5 Bengkulu City is not yet fully optimal. The library needs to address [or: improve] the library standards that have not yet been met to fully comply with the National Standard for Elementary School/Madrasah Ibtidaiyah Libraries for sustainable accreditation.